(untitled) (Polis (Santiago), 2018)
The author refers to the verse 13 of chapter 19 of the Gospel attributed to Matthew, which reads: "because whoever has, more will be given to him, and he shall have abundance: but whosoever hath not, even what he has will be taken", and links this to the sociology of science, stating the "Matthew effect"-eminent scientific researchers reap much more nourished applause, than other researchers, less known, for equivalent contributions- for exposing the social stratification of scientific communities.